(untitled) (International Journal of Engineering and Computer Science, 2015)
The application of ionizing radiation in medical sectors for imaging and treatment of patient is expanding day by day. Xray machines are very common modalities in medical facilities which provide diagnostic information about the human organs. On the other hand, different kinds of radioisotopes are utilized for imaging of patient organ in nuclear medicine. Some isotopes are also used for treatment purposes. However, during handling of radiological devices/radioisotopes radiation professional, patient, public may receive unwanted radiation exposure which can be harmful for them. However, there is an exposure limit for the occupational and public. Usually, there are two kinds of biological effects of radiation, one is deterministic and another stochastic. There is threshold level of radiation dose for the first one to occur but for the second one no limit of radiation dose. Even at small amount of dose stochastic effect may occur in the form of a genetic disorder and cancer disease. Therefore, assessment of radiation dose is always vital in the medical radiation facility. In the current study radiation dose is measured in some x-ray and nuclear medicine facilities by using two GM counters. It has been observed that occupational receive more radiation doses in nuclear medicine facilities compared to x-ray where as public receive fairly less amount of dose from the nuclear medicine activities. On the other hand, public is more vulnerable to radiation in x-ray facilities compared to nuclear medicine. Therefore, from the radiation safety point of view, to limit the exposure level of the concerned personnel is very important hence the adequate shielding arrangements should be in place according to national and international requirements.